MITIGATING THE IMPACT OF GENDER-BASED VIOLENCE IN SOUTH AFRICA: A SCOPING REVIEW OF PATRIARCHAL CULTURE (Proceedings of the International Conference on Gender and Sexuality, 2023)
Background Gender-based violence (GBV) remains a concerning issue globally with widespread prevalence in the South African context, due to both historical Apartheid and its traditional values. In addition, the socialization of gender, conventional expectations of femininity and masculinity, prejudice and gender stereotypes, the idea that the home is a private space run by men, and the general acceptance of violence as a part of public life, further create a society where GBV is rampant. Significant social, psychological, and physical impact on individuals and communities manifest as a violation of human rights.Method In a period where social justice is at the forefront of global policy and development work, this scoping review guided by Arksey and O'Malley aims to give a thorough overview of the scientific body of research on the following aspects in South Africa over the past ten years: men as viewed through a lens of economic power, and patriarchal culture as a social problem which South African men embody.Discussion Research, promoting legislative reforms, addressing GBV through educational programs that improve people's attitudes of violent behavior, and collaborating with political, non-governmental, and spiritual leaders are all effective ways to reduce violence against the vulnerable.Therefore, in conducting a scoping review, crucial gaps in interventions can be addressed. The framework by Arksey and O'Malley will be used to identify, select, and review relevant studies from various databases and sources. This study will make an important contribution towards achieving the Sustainable Development Goals (SDG’s) target of eliminating all forms of violence in Sub-Saharan Africa (SSA) by 2030.
Keywords: GBV; Social Justice; Gender norms; Abuse; Patriarchy; South Africa